The TyG index cutoff point and its association with body adiposity and lifestyle in children - Sarah A. Vieira‐Ribeiro; Poliana C.A. Fonseca; Cristiana S. Andreoli; Andréia Q. Ribeiro; Helen H.M. Hermsdorff; Patrícia F. Pereira; Silvia E. Priore; Sylvia C.C. Franceschini (Brazilian Society of Pediatrics, 2019)
Objective: To investigate the factors associated with insulin resistance in children aged 4-7 years, and to identify the cutoff point of the triglyceride‐glucose index for the prediction of insulin resistance in this population. Methods: A cross‐sectional study was conducted with 403 children from a retrospective cohort. Insulin resistance was also evaluated in a sub‐sample using the HOMA index. Four indicators of body adiposity were assessed: body mass index, waist‐to‐height ratio, and the percentages of total and central body fat. Food habits were evaluated by the identification of dietary patterns, using principal component analysis. Information was also collected on lifestyle, socioeconomic status, and breastfeeding time. Results: The median index observed in the sample was 7.77, which did not differ between the genders. The shorter the time spent in active activities, the higher the triglyceride‐glucose value; and increase in the values of body adiposity indicators was positively associated with triglyceride‐glucose. The cutoff point with the best balance between sensitivity and specificity values was 7.88 (AUC = 0.63, 95% CI: 0.51-0.74). Conclusion: The present study identified that total and central body adiposity and shorter time spent in lively activities was positively associated with insulin resistance, evaluated through the triglyceride‐glucose index. The cutoff point of 7.88 may be used in this population for insulin resistance risk screening, but caution is required when using it in other populations. Resumo: Objetivo: Investigar os fatores associados à resistência à insulina em crianças de 4 a 7 anos, e identificar o ponto de corte do índice triglicerídeos‐glicemia (TyG) para predição da RI nessa população. Métodos: Estudo transversal, com 403 crianças pertencentes a uma coorte retrospectiva. A resistência à insulina foi avaliada pelo índice triglicerídeos‐glicemia e também pelo índice HOMA, este em uma subamostra. Avaliou‐se quatro indicadores de adiposidade corporal: o índice de massa corporal, a relação cintura‐estatura e os percentuais de gordura corporal total e central. O hábito alimentar foi avaliado pela identificação dos padrões alimentares, utilizando‐se a análise de componentes principais. Foram coletadas também informações sobre estilo de vida, condição socioeconômica e tempo de aleitamento materno. Resultados: A mediana observada do índice triglicerídeos‐glicemia na amostra foi de 7,77 e não diferiu entre os sexos. Quanto menor o tempo diário em atividades ativas, maior o valor de triglicerídeos‐glicemia; e o aumento nos valores dos indicadores de adiposidade corporal associou‐se positivamente com o triglicerídeos‐glicemia. O ponto de corte com melhor equilíbrio entre os valores de sensibilidade e especificidade foi o de 7,88 (AUC = 0,63; IC 95% 0,51 ‐ 0,74). Conclusão: O presente estudo identificou que a adiposidade corporal total e central e o menor tempo diário em atividades ativas associou‐se positivamente com a resistência à insulina, avaliada pelo índice triglicerídeos‐glicemia. O ponto de corte de 7,88 pode ser utilizado nessa população para triagem do risco de resistência à insulina, mas é necessário cautela na sua utilização em outras populações. Keywords: TyG index, Adiposity, Lifestyle, Children, Palavras‐chave: Índice TyG, Adiposidade, Estilo de vida, Crianças